Study of postimplantation annealing of SiC - Avramenko, S.F.; Kiselev, V.S.; Romanyuk, B.N.; Valakh, M.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The implanted layer resistance R/□ thermoelectromotive force, optical transmittance T and open-circuit photovoltage measurements were made on epitaxial n-type 6H-SiC samples and Lely-grown 6H-SiC crystals implanted at 30o and 500 oC with Al ions annealed at 1600 to 2000 oC. The objective was to study processes of defect annealing and activation of implanted aluminum to determine the optimal parameters of the postimplantation annealing mode. It is shown that processes of radiation defect annealing and implanted aluminum activation are characterized by essentially different times that depend on the annealing and implantation conditions. Measurements of the open-circuit photovoltage U enable one to check the aluminum activation process and optimize the annealing conditions.